A cross-national investigation of university students' complaining behaviour and attitudes to complaining - Ferguson, Graham; Phau, Ian (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to investigate how students from Australia, Indonesia and Malaysia differ in their propensity to complain and attitudes to complaining. Design/methodology/approach – A self-administered questionnaire was designed using established scales to assess respondent reactions to a service failure by a university. The survey was completed by a sample of university students on an Australian university campus. ANOVA was used to compare differences between groups and regression was used to explore the relationship between attitudes and their complaining behaviours. Findings – Australian students have a less positive attitude to complaining than Malaysian and Indonesian consumers. Contrary to expectations, “switching” behaviours were not revealed as a separate dimension of complaining behaviours, however switching was identified with online complaining as part of a new complaining dimension related to taking action outside of the organisation. Malaysian and Indonesian students are more likely to complain in this way. Surprisingly, Indonesian students are less likely to remain loyal to the service provider and Australian students were less likely to “voice” internally to the service provider. Having a positive attitude to complaining was positively related to taking action outside the organisation and to voicing within the organisation, while negative attitudes to complaining were positively related to remaining loyal to the service provider for Australian and Malaysian students. Research limitations/implications – The findings are limited to consumers of complex services such as University degrees. They are also limited to Indonesian, Malaysian and Australian consumers. Other service contexts, cultures and product failure situations should be investigated in the future. Originality/value – This research bridges an inherent gap in the literature by exploring the complaining behavior of students in an Asia-Pacific context. Service organisations can use the findings to better interpret and respond to complaining behavior by students from different nationalities. In particular, it helps faculty and university administrators to manage dissatisfied students from diverse national backgrounds and assists marketers to develop marketing initiatives and communication policies for the student recruitment process.